Vietnam Labour Market and Informal Economy in a Time of Crisis and Recovery 2007-2009 : Main Findings of the Labour Force Surveys - Chi, Nguyen Huu; Huyen, Nguyen Thi Thu; Razafindrakoto, Mireille; Roubaud, Francois (World Bank, Washington, DC, 2017)
In 2007 the General Statistics Office (GSO) launched a joint research program with the French Institute of Research for Development (IRD) to measure and analyzes the informal sector in Vietnam. Two kinds of surveys were conducted in 2007: a national Labour Force Survey (LFS) which, in a first for Vietnam classified labour by institutional sector thereby separating out the informal sector; and two specific surveys in Hanoi and Ho Chi Minh City (HCMC) which were grafted onto the LFS2007 to find out more about the characteristics of household businesses (HB) in general and especially the informal sector (HB&IS2007). This brief presents the main findings (both methodological and analytical) of these two rounds of LFS as regards the labour market and the informal economy in Vietnam. In the context of the global crisis, it looks at the dynamics of the main labour market indicators with a special focus on informal sector and informal employment between 2007 and 2009.For the first time ever in Vietnam, it is possible measure precisely the evolution of the informal economy and to check for the robustness of the estimates provided. In the conclusion the author outline some of the implications of the findings in terms of survey design and economic and social policies.